2015
DOI: 10.3389/fncel.2014.00443
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophin as a central nervous system neuromodulator, evidences from the hippocampus

Abstract: Pleiotrophin (PTN) is a secreted growth factor, and also a cytokine, associated with the extracellular matrix, which has recently starting to attract attention as a significant neuromodulator with multiple neuronal functions during development. PTN is expressed in several tissues, where its signals are generally related with cell proliferation, growth, and differentiation by acting through different receptors. In Central Nervous System (CNS), PTN exerts post-developmental neurotrophic and -protective effects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 84 publications
0
66
0
Order By: Relevance
“…Pleiotrophin has several possible receptors, including protein tyrosine phosphatase receptor type ζ (PTPRZ), anaplastic lymphoma kinase (ALK), N-syndecan, neuroglycan, integrin αvβ3, and lipoprotein receptor-related protein (LRP) (González-Castillo et al, 2015), and as such, the functional effects of pleiotrophin binding are cell context-specific. Pleiotrophin was originally recognized to promote neurite outgrowth (Kinnunen et al, 1999; Li et al, 1990; Rauvala and Pihlaskari, 1987) and subsequently found to promote haptotactic neuroblast migration along radial glial processes from the subventricular germinal zone to the developing cortical plate during corticogenesis (Maeda and Noda, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Pleiotrophin has several possible receptors, including protein tyrosine phosphatase receptor type ζ (PTPRZ), anaplastic lymphoma kinase (ALK), N-syndecan, neuroglycan, integrin αvβ3, and lipoprotein receptor-related protein (LRP) (González-Castillo et al, 2015), and as such, the functional effects of pleiotrophin binding are cell context-specific. Pleiotrophin was originally recognized to promote neurite outgrowth (Kinnunen et al, 1999; Li et al, 1990; Rauvala and Pihlaskari, 1987) and subsequently found to promote haptotactic neuroblast migration along radial glial processes from the subventricular germinal zone to the developing cortical plate during corticogenesis (Maeda and Noda, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…PTN is an extracellular matrix protein that promotes neurite outgrowth [43] and that provides neuroprotection [44]. Additionally, PTN has been involved in neuronal plasticity during learning and also during recovery after lesion or in neuropathological situation functioning as a neuromodulatory peptide, particularly in the hippocampus [45]. The increase in PTN and the pNMDA receptor protein level explain best task performance of the MWM, a robust and reliable test that is strongly correlated with hippocampal synaptic plasticity and NMDA receptor function [46].…”
Section: Samp8mentioning
confidence: 98%
“…Pleiotrophin (PTN) is a secreted heparin‐binding growth factor known as a neuromodulatory peptide both in the central nervous system and in peripheral tissues . PTN is expressed in human skin cells, especially in high levels in fibroblasts.…”
Section: Fibroblastsmentioning
confidence: 99%
“…69 Pleiotrophin (PTN) is a secreted heparin-binding growth factor known as a neuromodulatory peptide both in the central nervous system and in peripheral tissues. [70][71][72] PTN is expressed in human skin cells, especially in high levels in fibroblasts. It inhibits melanogenesis through MITF degradation via the extracellular signal-regulated kinase (ERK)1/2 pathway in normal human melanocytes.…”
Section: Scf Edn1mentioning
confidence: 99%